2020
DOI: 10.1155/2020/2016809
|View full text |Cite
|
Sign up to set email alerts
|

Succinate Supplement Elicited “Pseudohypoxia” Condition to Promote Proliferation, Migration, and Osteogenesis of Periodontal Ligament Cells

Abstract: Most mesenchymal stem cells reside in a niche of low oxygen tension. Iron-chelating agents such as CoCl2 and deferoxamine have been utilized to mimic hypoxia and promote cell growth. The purpose of the present study was to explore whether a supplement of succinate, a natural metabolite of the tricarboxylic acid (TCA) cycle, can mimic hypoxia condition to promote human periodontal ligament cells (hPDLCs). Culturing hPDLCs in hypoxia condition promoted cell proliferation, migration, and osteogenic differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 46 publications
2
28
0
Order By: Relevance
“…Hypoxia‐mimicking agents, such as CoCl 2 , have been tried in the expansion of stem cells 24 . A previous study reported that CoCl 2 mimics the hypoxic state and promotes the proliferation, migration, and osteogenesis of mesenchymal stem cells by intracellular succinate–induced HIF‐1α stabilization 25 . This study, as a novel finding, showed that hypoxia increased the nuclear accumulation of RUNX2 during the early stages of PDLSC exposure, and it subsequently promoted osteogenic differentiation through the stimulation of osteogenesis‐related genes.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia‐mimicking agents, such as CoCl 2 , have been tried in the expansion of stem cells 24 . A previous study reported that CoCl 2 mimics the hypoxic state and promotes the proliferation, migration, and osteogenesis of mesenchymal stem cells by intracellular succinate–induced HIF‐1α stabilization 25 . This study, as a novel finding, showed that hypoxia increased the nuclear accumulation of RUNX2 during the early stages of PDLSC exposure, and it subsequently promoted osteogenic differentiation through the stimulation of osteogenesis‐related genes.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, GPR91 seems to be implied in the activation of coping mechanisms upon adverse conditions, including stimulation of proliferation of different cell types, migration, and angiogenesis [ 1 , 7 , 12 , 19 , 20 , 21 , 22 ]. This has also been illustrated in ischemic conditions [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen studies performed a comparison with normoxic conditions (20% or 21% oxygen), three used 1% oxygen, 20,24,28 five used 2% oxygen, 8,22,25,26,29 two used 3% oxygen, 12,30 and four studies compared various hypoxia levels, including 1%, 2%, and 5% oxygen; 37 1% oxygen and a reoxygenation group (from 1% to 20% oxygen); 8,15 and 5% and 1% oxygen. 31 Overall, 15 studies evaluated the effects of certain oxygen concentrations: 3 used 5% oxygen, 13,14,32 1 used 3% oxygen, 34 5 used 2% oxygen, 7,19,21,27,35 2 used 1% oxygen, 20,36 3 used less than 1% oxygen, [16][17][18] and another used less than 0.1% oxygen. 33…”
Section: Hypoxic Conditions (Oxygen Concentration)mentioning
confidence: 99%
“…28 Six studies reported an increase in osteogenic differentiation. 7,19,22,26,29,36 Hypoxic conditions also increased osteoclastogenesis, 17,27 improved the maintenance of pluripotent stem cells, 25 increased the expression of several mediators of apoptosis, and promoted tenocyte apoptosis. 20…”
Section: Main Outcomesmentioning
confidence: 99%